Porównanie układów technologicznych dużych instalacji kolektórów słonecznych współpracujących z węzłami ciepłowniczymi = Comparison of the large solar technological systems cooperating with the district heating nodes - Ziembicki, Piotr; Bernasiński, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the technological systems of large solar installations cooperating with district heating substations, which is dedicated for multi- family buildings. One of the topics mentioned in the paper is connected with using of computer simulation for the selection of these installations. In the article authors described the results of simulation and compared selected indicators characterizing these systems (efficiency, hot water solar fraction and water temperature in the tank and buffer).
Keywords: węzły ciepłownicze; energia odnawialna; kolektory słoneczne; sprawność systemu; symulacja komputerowa; district heating substations; renewable energy; solar collectors efficiency; systemefficiency; computer simulation